Classic papers on pelvic floor physiotherapy: the most frequently cited articles in three decades (1983–2013) - Fornari, Alexandre; Carboni, Cristiane (International Urogynecology Journal, 2018)
Introduction and hypothesis Pelvic floor physiotherapy has been utilized extensively over the past decades for the treatment of pelvic floor dysfunctions. The aim of this study was to identify and characterize the most frequently cited articles on pelvic floor physiotherapy published in the last 30 years. Methods A PubMed search of all articles published between 1983 and 2013 was performed. Articles with more than 100 citations were identified as “classic,” and were further analyzed based on author names, year of publication, journal of publication, subject, study design, country of research, and number of citations. In 2017, a new search for papers on pelvic floor physiotherapy was conducted using the same methods to compare them with the 2013 data. Results Of 1,285 articles published between 1983 and 2013, only 20 articles were cited more than 100 times. Among them, we found 12 randomized clinical trials (RCTs) and only 4 reviews. The most common topics among the classic articles were behavior therapy, pelvic floor muscle training (PFMT), biofeedback-assisted PFMT, and neuromuscular electrical stimulation. In 2017, we found 1,745 papers containing the term “pelvic floor physiotherapy,” indicating an increase of around 35% in 4 years. Conclusions Although there is a fast-growing number of publications, we still have few classic papers on pelvic floor physiotherapy, concentrated in a few research centers. However, the large number of RCTs shows that these papers have a high scientific level, confirming that they can be classified as classic papers.